Whaling days - Carrick, Carol; Frampton, David (New York : Clarion Books, 1993)
Surveys the whaling industry, ranging from hunting in colonial America to modern whaling regulations and conservation efforts
Includes bibliographical references (p. 39) and index
Keywords: Whaling -- Juvenile literature; Whaling -- United States -- Juvenile literature; Whales -- Juvenile literature